Graphene oxide organogel electrolyte for quasi solid dye sensitized solar cells - Gun, Jenny (2013)
Low concentration, as low as 0.4 wt.% graphene oxide organogels is reported for different organic solvents. The gelation of organic solvents at exceedingly low concentrations opens the door for the implementation of graphene oxides based electrolytes in various electrochemical applications. Here we demonstrate the use of acetonitrile–graphene oxide (GO) gel containing iodide/triiodide as a quasi-solid electrolyte for dye sensitized solar cells (DSCs). Electrochemical impedance studies reveal that the mass transfer barrier is not adversely affected by the presence of the minute amount of GO gel former. The achieved energy conversion efficiency (η) for the device without GO and with 1% GO gel electrolytes is 6.9% and 7.5% respectively under one sun illumination.